Childfree as a Modern Life Option: An Analysis of Islamic Law and Psychology on Contemporary Social Phenomena - Muhammad Husni Abdulah Pakarti; Ija Suntana; Irfan Fahmi; Encup Supriatna; Yernar Yessimkulov (al-Battar: Jurnal Pamungkas Hukum, 2026)
The phenomenon of childfree or the conscious decision not to have children is becoming an increasingly prominent social issue in modern society, including in Indonesia. This decision gave rise to normative, moral, and psychological debates in society based on religious values. This study aims to analyze the phenomenon of childfree from the perspective of Islamic law and psychology, in order to understand how this life choice can be accepted or rejected within the framework of religious values and individual psychological well-being. The research uses a qualitative approach with the library research method through descriptive analysis of Islamic legal literature, maqāṣid al-syarī'ah theory, and studies of modern psychology and Islamic psychology. The results of the study show that in Islamic law, childfree can be categorized as a decision that is mubah as long as it is based on considerations of benefits such as health, emotional stability, or economic factors, and does not contradict the principles of maqāṣid al-syarī'ah. From a psychological perspective, these decisions are closely related to the factors of mental readiness, social pressure, and the need for self-actualization that reflect the process of finding a balance in life and personal happiness. Meanwhile, from the socio-religious side, this phenomenon still causes stigma because it is considered deviant from cultural norms and religious values that place children as a symbol of family success. Thus, the phenomenon of childfree requires a holistic and moderate approach in order to understand the proportionate relationship between individual freedom, social welfare, and Islamic spiritual values.